PENGARUH LATIHAN SINGGLE LEG STRIDE JUMP DAN QUICK LEAF TERHADAP PENINGKATAN POWER OTOT TUNGKAI ATLET BOLA VOLI KUMBUNG TAHUN 2022 - Sukarman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
The results of field observations that the Kumbung volleyball athlete's condition of leg muscle power is still not optimal, where in the last match the physical and jumping of volleyball athletes decreased so we need to conduct an evaluation, the most basic technique is related to the athlete's physical problems, especially leg muscle power where the role of muscle power is This leg is very important in addition to doing a jump smash it is also used to block the opponent's attack from above the net. Single leg stride jump and quick leaf plyometric exercises are a form of exercise to improve the leg muscle power of volleyball players. The objectives to be achieved in this study were to find out the effect of single leg stride jump exercise on increasing the leg muscle power of the 2022 Kumbung volleyball athlete and to find out the effect of quick leaf exercise on the increase in leg muscle power of the 2022 Kumbung volleyball athlete. Experimental research